Comparing horizontal versus vertical arrangement on the ground resistance values - Shamsul, Syakir Azim; Muhammad, Usman; Aman, Fazlul; Mohamad Nor, Normiza; Osman, Miszaina (Institute of Advanced Engineering and Science, 2024)
It is important to compare the horizontal electrodes versus vertical ground electrodes particularly when there is limited area to extend the horizontal ground electrode and hard soil at the deeper soil in order to install the vertical rod electrode. Although all of these can be assessed by computational work, much work has shown that computed resistance values are different than measured resistance values and these computational softwares are not always available to the users. For these reasons, the aim of this paper is to address this shortfall by considering two sites with two-layer soil resistivity model where site 1 with upper layer higher than the lower layer and vice versa for site 2. For the same size of ground electrodes, vertical arrangement is found to have lower ground resistance values, despite higher soil resistivity at the lower layer soil. Soil compaction after backfilling the trench during the installation of horizontal electrode has been identified as the main factor that contributes to differences between the measured and computed resistance values.